2018
DOI: 10.1111/1467-6427.12202
|View full text |Cite
|
Sign up to set email alerts
|

Ideas of the change process: family and therapist perspectives on systemic psychotherapy for children with conduct disorder

Abstract: This report is based on a small‐scale qualitative study exploring therapist and client perspectives on the therapeutic change process in home‐based family therapy for children with conduct disorder. The study consisted of focus group discussions with therapists, interviews with client families and audiotaped therapy sessions. The findings suggested that home‐based therapy (home visits) was effective in improving hard‐to‐reach clients’ access to help, resources, and opportunities, as well as the therapists’ acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…While Tighe at al. (2012) suggested a unidirectional relationship whereby parent change influences youth change, other research has suggested it is more reciprocal (Morino, 2019). Kaur, Pote, Fox, and Paradisopoulos (2017) described parents/caregivers’ perspectives on change in MST, while identifying parental change as an important factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While Tighe at al. (2012) suggested a unidirectional relationship whereby parent change influences youth change, other research has suggested it is more reciprocal (Morino, 2019). Kaur, Pote, Fox, and Paradisopoulos (2017) described parents/caregivers’ perspectives on change in MST, while identifying parental change as an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…Youth with CD and their families present with substantial treatment challenges and a remarkable unresponsiveness to treatment (Fairchild et al, 2019; Sexton & Datchi, 2014). Adverse cycles of missed appointments and recurrent non‐attendance to therapy sessions result in repeated referrals and worsening problems (Morino, 2019; Sexton & Datchi, 2014). Research shows the success of standard intervention programs (e.g., Triple P; Sanders, Kirby, Tellegen, & Day, 2014) is limited to younger children with less severe externalising behaviours (Sexton & Lebow, 2016).…”
Section: Active Ingredients In Family Therapy For Conduct Disordermentioning
confidence: 99%
See 2 more Smart Citations